Population based analysis of gender disparities in 23,715 percutaneous endovascular revascularisations in the metropolitan area of Hamburg - Behrendt, Christian-Alexander; Bischoff, Moritz; Schwaneberg, Thea; Hohnhold, Rainer; Diener, Holger; Debus, Eike Sebastian; Rieß, Henrik C. (European journal of vascular and endovascular surgery, 2019)
Background - The worldwide prevalence of peripheral artery disease (PAD) is increasing and endovascular revascularisation (ER) has become the primary invasive treatment option. This study aims to illuminate gender disparities in ER of PAD. - Methods - This is a retrospective, cross sectional study design. All inpatient invasive, percutaneous endovascular treatments of PAD conducted in the metropolitan area of Hamburg (Germany) were collected consecutively between 01/2004 and 12/2015. Relevant socio-demographic risk factors, technical assessments, procedural details, and in hospital outcomes were collected and subsequently analysed. - Results - A total of 23,715 ERs were identified (39.7% females). Female patients were older (74 vs. 70 years, p < .001) and more often suffered from rest pain (12.0% vs. 9.7%, p < .001) at the time of presentation. No differences were found for index lesion complexity (Trans-Atlantic Inter-Society Consensus classes) and the ankle brachial index was less often stated not to be valid in females (5.9% vs. 7.1%, p = .005 for intermittent claudication; 28.5% vs. 32.0%, p = .001 for chronic limb threatening ischaemia, CLTI). If the ER was performed for CLTI, crural vessels below the knee were less often revascularised in females (32.2% vs. 42.7%, p < .001). Peri-operative major bleeding complications including pseudoaneurysms occurred twice as often in females, and female gender was an independent predictor of bleeding complications in the adjusted analyses (OR 2.32, 95% CI 1.49-3.64, p < .001 for IC; OR 1.67, 95% CI 1.10-2.53, p = .017 for CLTI). Lastly, females were more often transferred to nursing homes when compared with males (0.3% vs. 0%, p = .001 for IC; 2.5% vs. 1.2%, p < .001 for CLTI). - Conclusion - In this study considering percutaneous ER for PAD, female patients were older, had different clinical symptoms, suffered more often from complications, and were at risk of social isolation after discharge when compared with their male counterparts. These results emphasise the need for further studies to evaluate a gender based treatment algorithm in PAD.